2012
DOI: 10.1080/87567555.2011.633943
|View full text |Cite
|
Sign up to set email alerts
|

Silence in Teaching and Learning: Perspectives of a Nepalese Graduate Student

Abstract: The nature of silence is complex in any classroom with international or domestic students. Instructors sometimes fail to recognize that the classroom silence of foreign students is unlike their native counterparts. With an insider perspective, this article explores the concept of silence among international students by examining the existing body of literature relating to cultural norms. It also suggests a number of ways of dealing with silent students in a diverse classroom setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Studies indicate that both cultural and educational background and lack of English communicative skills are traditional causes of students' silence in their classroom. Majority of the Asian non-native English speaking students has a set of drawbacks which act as stumbling blocks to their progression in learning (Bista, 2012). Multiple proportions of silence have been found from the experiences of non-native English speaking students in their academic courses in Tatar's study.…”
Section: Analysis Of the Causes Of Learners' Silencementioning
confidence: 99%
“…Studies indicate that both cultural and educational background and lack of English communicative skills are traditional causes of students' silence in their classroom. Majority of the Asian non-native English speaking students has a set of drawbacks which act as stumbling blocks to their progression in learning (Bista, 2012). Multiple proportions of silence have been found from the experiences of non-native English speaking students in their academic courses in Tatar's study.…”
Section: Analysis Of the Causes Of Learners' Silencementioning
confidence: 99%
“…While English comprehension in the southeast is challenging, the anxiety created by the language barrier drastically increases when students are asked to participate in formal oral discussions (Bista, 2012). However, research has shown that informal conversations, such as those found with patients and peers in clinical practice, can greatly increase communication skills (Lee, 2016;Mesaroli et al, 2015).…”
Section: Communication Challengesmentioning
confidence: 99%
“…To further combat various communication issues, faculty should pay special attention to student participation levels during group discussions or patient interactions. Although international students typically study English for years prior to studying abroad, many are apprehensive and reluctant to participate in discussions due to their perceived (or realistic) shortcomings (Bista, 2012). However, studies show that communication skills greatly increase with extended use, so students should be encouraged to practice these skills (Lee, 2016;Mesaroli et al, 2015).…”
Section: Communication Challengesmentioning
confidence: 99%
“…International students with a lower level of English proficiency often experience difficulties in class participation. In addition, international students often struggle with cultural differences, including social expectations of interaction, educational values, and teachercentered pedagogies (Bista, 2012). Moreover, some international students spend more than 5 hours per day studying.…”
Section: Literature Reviewmentioning
confidence: 99%